A female patient with hypokalaemia-induced J wave syndrome: An unusual case report. Issue 38 (September 2017) - Wang, Aqian; Li, Xiang; Dookhun, Muhammad Nabeel; Zhang, Tiancheng; Xie, Ping; Cao, Yunshan
Abstract: Rationale: Prominent J waves can be seen in life-threatening cardiac arrhythmias such as Brugada syndrome, early repolarization syndrome, and ventricular fibrillation. We herein present an unusual case report of hypokalemia-induced J wave syndrome and ST (a part of ECG) segment elevation. Patients concerns: A 52-year-old woman with chief complaints of chest pain for 2 hours and diarrhea showed a marked hypokalemia (2.8 mmol/L) and slightly elevated creatine kinase-MB (CK-MB) (57.5 U/L). The electrocardiographic (ECG) recording was normal upon admission and computed tomography (CT) aorta angiography excluded an aorta dissection. ECG done 17 hours after admission showed ST segment elevation and elevated J wave in leads II, III and aVF, and fusion of T and U wave in all leads. Diagnosis: We first thought that the diagnosis of this patient was acute myocardial syndrome. Intervention: Potassium chloride and oflocaxin treatment was given to the patient. Outcomes: Laboratory test showed the level of serum potassium ion increased to 3.4 mmol/L and CK-MB did not have any significant change. The infusion of potassium chloride-induced disappearance of the elevated J wave, although QT (a part of ECG) intervals were still longer than that upon admission. Lessons: This case tells us that hypokalaemia might induce J wave and elevated ST segments which should be distinguished from acute myocardial syndrome.